Analytical modelling of cold-formed steel-to-timber connections with inclined screws. (15th December 2021) - Vella, Nathan; Gardner, Leroy; Buhagiar, Spiridione
Highlights: EN 1995 design expressions underestimate ultimate loads and overestimate slip moduli. Analytical model validated against available push-out test results. Analytical model can accurately describe the ultimate load and the slip moduli. Analytical model can accurately predict failure modes. Proposed model offers a significant improvement over current design provisions. Abstract: An analytical model that can describe the load-slip response of cold-formed steel-to-timber connections, based on three components: timber embedment, screw bending and the axial pull-through, is presented. The model takes into consideration the screw inclination and the damage to the timber caused during the screw drilling process. The model was validated against available push-out test results, where it was shown that the model can accurately describe the ultimate load, the slip at ultimate load, and the two slip moduli, ks and ks, m, with mean model-to-test ratios of 1.01, 1.03, 1.09 and 0.96, respectively. The observed failure modes were also accurately predicted. Comparisons between the test data and the predictions of the EN 1995-1-1 design expressions showed that the Eurocode underestimated the ultimate loads by around 50% on average and overestimated the slip moduli by around 500% on average; the proposed model therefore offers a significant improvement over current design provisions.